Strategi Pemasaran untuk Meningkatkan Penjualan Mahalona Kopi Karawang - Rievansyah Adhitiasaputra; Enjang Suherman; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implication for Mahalona Kopi is that it needs to design more competitive marketing strategies and offer products or services to potential markets. This research aims to formulate a marketing strategy for Mahalona Kopi and take advantage of opportunities and overcome challenges so that the coffee shop business can continue to operate and generate profits. The data processing method used in this research is descriptive qualitative method, with the analysis process using SWOT analysis. Data sources include primary data and secondary data, obtained through direct observation and in-depth interviews related to opportunities and challenges in the coffee shop business. The matrix results show that Mahalona Kopi is in cell IV (Grow and Build). The appropriate strategy for this cell position at Mahalona Kopi is an intensive strategy, such as market penetration, product development, and market development.